Regulatory frameworks involved in the floral induction, formation and developmental programming of woody horticultural plants: a case study on blueberries - Song, Guo-qing; Liu, Zongrang; Zhong, Gan-yuan (Frontiers in Plant Science, 2024)
Flowering represents a crucial stage in the life cycles of plants. Ensuring strong and consistent flowering is vital for maintaining crop production amidst the challenges presented by climate change. In this review, we summarized key recent efforts aimed at unraveling the complexities of plant flowering through genetic, genomic, physiological, and biochemical studies in woody species, with a special focus on the genetic control of floral initiation and activation in woody horticultural species. Key topics covered in the review include major flowering pathway genes in deciduous woody plants, regulation of the phase transition from juvenile to adult stage, the roles of CONSTANS (CO) and CO-like gene and FLOWERING LOCUS T genes in flower induction, the floral regulatory role of GA-DELLA pathway, and the multifunctional roles of MADS-box genes in flowering and dormancy release triggered by chilling. Based on our own research work in blueberries, we highlighted the central roles played by two key flowering pathway genes, FLOWERING LOCUS T and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1, which regulate floral initiation and activation (dormancy release), respectively. Collectively, our survey shows both the conserved and diverse aspects of the flowering pathway in annual and woody plants, providing insights into the potential molecular mechanisms governing woody plants. This paves the way for enhancing the resilience and productivity of fruit-bearing crops in the face of changing climatic conditions, all through the perspective of genetic interventions.